États-Unis : huit thématiques clés de la sociologie du travail - Arne L. Kalleberg; Kevin T. Leicht (La Nouvelle Revue du Travail, 2021)
The paper discusses changes in the United States’ main sociology of work themes since World War II. The discipline is broadly conceptualised here as a study of jobs and organisations and of their linkage, inter alia, to social stratification and inequality, economic policy and worker power. We identify eight main themes: work organisation and the labour process; labour markets and professional mobility; professions and professional work; employment relations; the meaning of work; unions and worker power; workplace stratification and inequality; and workforce diversity. For each theme, a summary is offered encapsulating the main issues, research questions and studies, all revealing important aspects of work in the United States. These themes are likely to remain important to the sociology of work in the United States for years to come.